2019
DOI: 10.1186/s13071-019-3367-1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and multilocus genotyping of Giardia duodenalis in black-boned sheep and goats in southwestern China

Abstract: BackgroundGiardia duodenalis is an important intestinal protozoan infecting both humans and animals, causing significant public health concern and immeasurable economic losses to animal husbandry. Sheep and goats have been reported as common reservoirs of G. duodenalis, but only a limited amount of information is available for native breeds of these small ruminants in China. The present study investigated the prevalence and multilocus genotypes of G. duodenalis in black-boned sheep and goats, two important nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 63 publications
5
11
0
Order By: Relevance
“…Giardia duodenalis assemblages A, B and E were identified, and G. duodenalis assemblage E was the dominant assemblage found in this study, which is consistent with previous reports [ 6 , 7 , 25 ]. Giardia duodenalis assemblages A and E were identified as the two most common assemblages in sheep, goats and cattle, with assemblage B reported occasionally [ 11 , 25 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Giardia duodenalis assemblages A, B and E were identified, and G. duodenalis assemblage E was the dominant assemblage found in this study, which is consistent with previous reports [ 6 , 7 , 25 ]. Giardia duodenalis assemblages A and E were identified as the two most common assemblages in sheep, goats and cattle, with assemblage B reported occasionally [ 11 , 25 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Giardia duodenalis was initially screened via nested PCR amplification targeting the bg [ 7 ] gene, and then studied by a MLG analysis based on the gdh [ 4 ] and tpi [ 28 ] genes. After amplification, the DNA fragments were separated by agarose gel electrophoresis (1% agarose) stained with DNA Green (TIANDZ, Beijing, China) and observed using a Tanon 3500 Gel Image Analysis System (TANON, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two novel subtypes (named as E45*, n = 4 and E46*, n = 1) and 3 novel subtypes (named as E42*, n= 5; E43*, n= 2 and E44*, n= 1) of assemblage E were identified at the gdh and tpi loci, respectively (Table 2). Previous studies have shown that the assemblage E is the primary genotype in different animals [1,[39][40][41][42][43][44][45]. Both assemblage A and assemblage E were also found in humans [1,5].…”
mentioning
confidence: 91%
“…However, to date there have been only six reports on G. duodenalis infection from six Chinese provinces (Xinjiang, Heilongjiang, Liaoning, Henan, Jilin, and Shandong) [30,41,42,56,70,71]. In this study, the prevalence and genetic diversity of G. duodenalis in farmed rabbits from Shaanxi province were investigated using a multilocus genotyping tool [11,43,67].…”
Section: Introductionmentioning
confidence: 99%